2013
DOI: 10.1111/liv.12091
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and prediction of HBsAg loss during therapy with analogues in patients affected by chronic hepatitis B HBeAg negative and genotype D

Abstract: HBeAg negative patients infected by HBV genotype D should be treated with more potent NAs such as entecavir or tenofovir to obtain a significant qHBsAg decrease, but the achievement of HBsAg loss seems to require almost two decades of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 17 publications
4
29
0
1
Order By: Relevance
“…These results are not surprising because they are similar to those reported by Boglione et al [8], who showed that ADV had a better serological response than virological response. The potency of LAM on HBsAg reduction was also demonstrated by the study of Seto et al [19], who showed a similar median HBsAg decline rate (0.10 log 10 IU/mL/year) during a 10-year treatment with LAM in patients who had responded to LAM favorably.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are not surprising because they are similar to those reported by Boglione et al [8], who showed that ADV had a better serological response than virological response. The potency of LAM on HBsAg reduction was also demonstrated by the study of Seto et al [19], who showed a similar median HBsAg decline rate (0.10 log 10 IU/mL/year) during a 10-year treatment with LAM in patients who had responded to LAM favorably.…”
Section: Discussionsupporting
confidence: 91%
“…HBsAg kinetics and prediction of HBsAg loss were demonstrated only during the short-term treatment with individual NAs [8], [9]. However, whether ETV or TDF is more potent toward HBsAg reduction than LAM or ADV remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of PEG-IFN is limited in the hepatitis e antigen (HBeAg)-negative patients for the low rate of virological response and the sideeffects associated with the subcutaneous administration (Zoulim and Perrillo, 2008). Therefore, NAs were the most used treatments in HBeAg-negative patients, but the HBsAg decrease is very poor (Boglione et al, 2013;Chevaliez et al, 2013;Wong et al, 2013) and the HBsAg loss is difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of PEG-IFN is limited in the hepatitis e antigen (HBeAg)-negative patients for the low rate of virological response and the sideeffects associated with the subcutaneous administration (Zoulim and Perrillo, 2008). Therefore, NAs were the most used treatments in HBeAg-negative patients, but the HBsAg decrease is very poor (Boglione et al, 2013;Chevaliez et al, 2013;Wong et al, 2013) and the HBsAg loss is difficult to achieve.The PEG-IFN therapy could be optimized by selection of patients with best chance of response using baseline predictive factors (Krishnamoorthy and Mutimer, 2015), while host genetic factors as interleukin (IL)28B were analyzed in some studies but without reliable results (Boglione et al, 2014b;Galmozzi et al, 2014;Lampertico et al, 2013). Other promising predictive marker of HBsAg loss seems to be the serum level of interferon-inducible protein 10 (IP10), but has been studied only during NAs therapy .…”
mentioning
confidence: 99%
“…The currently available data would suggest otherwise: HBsAg seroclearance is considered a rare event during NA therapy; this event is observed in only 0.5-1% of all treated patients per year. The rate of decline of serum HBsAg levels is such that, according to mathematical models, a complete elimination could theoretically be achieved in a time frame of 20-30 years [18,19]. This effect could be expected for both HBeAg-positive and HBeAg-negative CHB.…”
Section: Current Hbv Therapiesmentioning
confidence: 94%